Upaya Memperbaiki Kedisiplinan Mahasiswa Dalam Melaksanakan Praktik Klinik Keperawatan di Akper William Booth Surabaya - ENY, STEVANUS, WINDHU, ENY, STEVANUS, WINDHU (D3 Kebidanan, 2012)
Disciplinary culture today has not been fully realized, both within the family, community, or in environmental education. Meanwhile, in the university found many violations of the order of the campus. Students need an awareness from within themselves to comply with all regulations and order of education. In the world of education, realizing that education still needs to improve his discipline. Because college is a very strategic educational institutions to instill discipline and teach. The purpose of this research is to develop efforts to improve student discipline Nursing Academy William Booth Surabaya in clinical nursing practice based on analysis of individual factors (attitudes toward behavior, subjective norms and perceptions of control), and Organizational Factors affecting student discipline. This study is an observational analytic method. Based on the time, this study is Cross Sectional where data is drawn together in a certain period and the population in this study is the third level students of the school year 2010-2011 Nursing Academy William Booth Surabaya, as many as 40 people to sample 36 respondents and the sampling technique that is simple random sampling. The results showed that the factors controlling attitudes and behaviors significantly influence the intention to practice nursing clinic, Intention (Intension) students significantly influence discipline in performing clinical nursing practice. Organizations Nursing Academy punishment significantly affect the discipline of nursing students carry out clinical practice, clinical supervisor practice land factors significantly affected the discipline of nursing students carry out clinical practice. Thus educational institutions need to revisit policies on the implementation of nursing clinical practice in accordance with the requirements for clinical practice of nursing by students can come to fruition. And future research agenda of this research can be done through the comparison of results before and after monitoring of the discipline of nursing students in clinical practice.Keywords : Discipline, nursing clinical practice.